2020
DOI: 10.1021/acs.jchemed.0c00554
|View full text |Cite
|
Sign up to set email alerts
|

An International Perspective: Teaching Chemistry and Engaging Students During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has caused the loss of many lives and transformed the global educational system. This has resulted in a rapid transition from face-to-face classroom meetings to online education delivery. Online education provides another opportunity to engage students during crises, such as pandemics. However, during the transition to online education, both students and educators faced tremendous challenges, especially at rural locations. To shed light on these experiences, we conducted a survey to learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
1
36
0
1
Order By: Relevance
“…The most direct approach to creating a new instrument is to draw on observations and holistic impressions and use good judgement (e.g. Chen, Kaczmarek, and Ohyama 2020;Dietrich et al 2020;Tigaa and Sonawane 2020;Asgari et al 2021). Authors like Buttler, George, and Bruggemann (2021) had time to test their questionnaire in a pilot study, but noted that previous literature on emergency remote teaching was not yet available to use as a foundation for their approach.…”
Section: Introductionmentioning
confidence: 99%
“…The most direct approach to creating a new instrument is to draw on observations and holistic impressions and use good judgement (e.g. Chen, Kaczmarek, and Ohyama 2020;Dietrich et al 2020;Tigaa and Sonawane 2020;Asgari et al 2021). Authors like Buttler, George, and Bruggemann (2021) had time to test their questionnaire in a pilot study, but noted that previous literature on emergency remote teaching was not yet available to use as a foundation for their approach.…”
Section: Introductionmentioning
confidence: 99%
“…Participants came to understand that there is an urgency to centering something useful, beneficial and flexible to engage the learning process and build a sense of responsibility, both lecturer and students, to undertake effective online learning. Educators' leadership of engaging students with the learning process indeed plays a vital role in these unprecedented times (Tigaa & Sonawane, 2020).…”
Section: Agility and Adaptabilitymentioning
confidence: 99%
“…Losing access to student housing and meal plans contributed to housing and food insecurities for many students, including low-income students and international students [22,23], and heightened housing and food insecurities impacted off-campus students as well [24]. Moreover, poor internet connection and lack of a quiet or safe space to study made it more difficult for students to complete their assignments and succeed during remote instruction [25][26][27][28]. For example, one recent study of college students in introductory sociology courses showed that more than 50% of all students experienced occasional internet problems during remote learning in Spring 2020 [29].…”
Section: Introductionmentioning
confidence: 99%